Draft Annual Plan 1993-94 Volume I Government of Karnataka Planning Department - Planning Commission (Planning Commission, 1992)
Eighth Five Year Plan of Karnataka 1992-97 is approved for an outlay of Rs.12300 crores at 1991-92 prices compared to Rs.3575 crores at 1984-85 prices for the Seventh Five Year Plan. Thus the Eighth Plan envisages a big step up in State plan investment, more than double in real terms over that of Steventh Plan. There was a significant shortfall in plan investment during the Seventh 'Plan resulting in, among other things, a sluggish development of the core infrastructural sectors like Power and Irrigation.
Government of Karnataka Planning Department